Representational exchange and edgework: towards theorising the coping with fragmentary information - Isto Huvila (Information Research: An International Electronic Journal)
Introduction. People face often situations when the available information is fragmentary and epistemically and ontologically different stemming from multiple incongruous systems of knowledge. While this is obvious on the basis of the vast corpus of information behaviour research to date, relatively little attention has been conducted so far to explicate the mechanisms of how people routinely manage to use such unsatisfactory sources in their pursuits.